Morphology, micromorphology and physicochemical properties of Annona squamosa L. (Annonaceae) leaves from Vietnam - Ha, Ly Hong Huong; Thu, Do Thi Anh; Vu, Tran Anh; Lam, Duong Nguyen Xuan; Thuy, Ho Thi Thach; Vinh, Vo Hien (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Introduction: In everyday life, nature has given us countless useful medicinal plants. Among the common plants in Vietnam, the custard apple (Annona squamosa L.) has not been mainly used as a fruit but also traditionally as a medicine. However, studies on morphological characteristics remain limited in Vietnam as well as around the world. Objective: Determine the morphological and microscopic characteristics, and physicochemical features of A. squamosa leaves. Materials and methods: A. squamosa leaves, morphological research process (analysis and photography), microscopic analysis process (staining leaf microscopic specimens and microscopy), physicochemical properties (described in Vietnamese Pharmacopoeia V). Results: The characteristics of A. squamosa leaves were described in detail such as morphology, cross-sections, leaf powder composition, and purity of herb. Conclusion: The morphological, microscopic components and components in medicinal powder will help create the basis for building testing standards for this medicinal plant in the future as well as support further research on A. squamosa species in Vietnam.